Evaluasi Dampak Pelatihan Pembuatan Alat Evaluasi Pembelajaran Berbasis AI dalam Mendukung Pencapaian SDGs - Nanda, Hanjar Ikrima; Miftakh, Eliza Silviana; Febriani Putri, Sheila; Wardoyo, Cipto; Mustofa, Muhammad Ifan Ali; Zulfida, Bilqis Rizqia (Jurnal SOLMA, 2025)
Background: This community service activity aims to improve teacher competence in utilizing AI in the classroom learning evaluation process. The utilization of technology-based learning evaluation tools by Malang City Accounting MGMP teachers is still limited due to limited time in preparing technology-based evaluation tools and lack of access to practical training that is relevant to the accounting curriculum. Methods: The methods used include FGDs, preparation of activities and preparation of materials, training, and evaluation with participants totaling 15 accounting teachers in Malang City. Activities were carried out from April to June 2025. Results: The results of the training showed that 82.84% of participants responded positively to the ease, efficiency, and benefits of using AI technology in supporting the learning evaluation process. Participants felt motivated, comfortable and eager to apply the tools introduced. However, teachers' technical skills in using the technology still need strengthening. Conclusions: The success of this program is not only can be seen from the increase in participants' ability to develop technology-based learning evaluation tools, but also from changes in evaluation methods used by teachers to be more varied and adapt to technological developments.